The effective CIO how to achieve outstanding success through strategic alignment, financial management, and IT governance - Brown, Eric J. (CRC Press, 2009)
Links theoretical scaffolding with effective IT management implementation. This title helps to dissolve the negative image many CIOs have as remote, purely rational decision machines, while demonstrating how to improve quality and throughput in your business. It includes interviews with highly successful CIOs.
Includes bibliographical references (pages 315-316) and index. - Print version record
Keywords: Chief information officers; Information technology -- Management; Information resources management; Chefs des services de l'information; Technologie de l'information; Gestion; Gestion de l'information; BUSINESS & ECONOMICS; Information Management; BUSINESS & ECONOMICS; Knowledge Capital; Information technology; Management